What is the Impact of Investment on Labor Income? - Chortareas, Georgios; Noikokyris, Emmanouil (World Bank, Washington, DC, 2018)
This study investigates empirically the determinants of labor shares focusing on the role of investment and exchange rate volatility. The authors use a system GMM panel approach and consider 34 Organization for Economic Co-operation and Development (OECD) countries along with South Africa for the period 1995-2015. The authors results reveal that the level of a country’s investment is a significant factor driving changes in the labor share of income. This evidence is in line with the theoretical mechanism for the role of investment presented by Lawrence (2015). While the authors consider several other factors, suggested by the extant empirical literature, the authors only find evidence for the degree of a country’s exposure to the international financial system, which is inversely related with labor shares. This study is a background note for the South Africa systematic country diagnostic.